-78+66x-21x+20-47+88x=10x-36x+18

Simple and best practice solution for -78+66x-21x+20-47+88x=10x-36x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -78+66x-21x+20-47+88x=10x-36x+18 equation:


Simplifying
-78 + 66x + -21x + 20 + -47 + 88x = 10x + -36x + 18

Reorder the terms:
-78 + 20 + -47 + 66x + -21x + 88x = 10x + -36x + 18

Combine like terms: -78 + 20 = -58
-58 + -47 + 66x + -21x + 88x = 10x + -36x + 18

Combine like terms: -58 + -47 = -105
-105 + 66x + -21x + 88x = 10x + -36x + 18

Combine like terms: 66x + -21x = 45x
-105 + 45x + 88x = 10x + -36x + 18

Combine like terms: 45x + 88x = 133x
-105 + 133x = 10x + -36x + 18

Reorder the terms:
-105 + 133x = 18 + 10x + -36x

Combine like terms: 10x + -36x = -26x
-105 + 133x = 18 + -26x

Solving
-105 + 133x = 18 + -26x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26x' to each side of the equation.
-105 + 133x + 26x = 18 + -26x + 26x

Combine like terms: 133x + 26x = 159x
-105 + 159x = 18 + -26x + 26x

Combine like terms: -26x + 26x = 0
-105 + 159x = 18 + 0
-105 + 159x = 18

Add '105' to each side of the equation.
-105 + 105 + 159x = 18 + 105

Combine like terms: -105 + 105 = 0
0 + 159x = 18 + 105
159x = 18 + 105

Combine like terms: 18 + 105 = 123
159x = 123

Divide each side by '159'.
x = 0.7735849057

Simplifying
x = 0.7735849057

See similar equations:

| -3m=8n-1 | | -5r+8=43 | | 9k-7=21-3k | | 1.7t+8-1.62=0.4t-0.32+8 | | 7h+3=0 | | 37=x+3+2x+2+5x | | m=2-1.25(-1) | | 5y-3+y=90 | | 80-3k=5k+8 | | -22+14x-33+10x-77+25x=88-14x+65-5+35 | | 2(2d-7)=(2+4d)2 | | 2x+32=6x+8 | | w^2+2w-310=0 | | 2w-9=-17 | | 5w^2+30w+6=0 | | 16x(7-x)=160 | | 8x-2=28x+13 | | 9*(3x)+4*(3x)=30x+5 | | (4x+34)=(7x+10) | | 9y+5y+20=62 | | 3x-10x+16=9-12x-28 | | 6(x-1)=3(x+1) | | 5xy(x+y)= | | (y-2)(y+4)=0 | | 6=2(7-c) | | y=16-6 | | 8-23x-14=9x-30x-6 | | 25-1.25x=16-.5x | | 15x-20=14x-21 | | 7+x(4)=16 | | -5n-8=16m | | 4x-5-6=12x-x-4-3x-7 |

Equations solver categories